2012
DOI: 10.1038/nm.2717
|View full text |Cite
|
Sign up to set email alerts
|

NLRP3 has a protective role in age-related macular degeneration through the induction of IL-18 by drusen components

Abstract: Age-related macular degeneration (AMD) is the leading cause of central vision loss worldwide. Drusen accumulation is the major pathological hallmark common to both dry and wet AMD. Although activation of the immune system has been implicated in disease progression, the pathways involved are unclear. Here we show that drusen isolated from donor AMD eyes activates the NACHT, LRR and PYD domains-containing protein 3 (NLRP3) inflammasome, causing secretion of interleukin-1β (IL-1β) and IL-18. Drusen component C1Q … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

27
449
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 386 publications
(479 citation statements)
references
References 50 publications
27
449
3
Order By: Relevance
“…The consequence is a switch to a more 'classical' chronic inflammatory responses propagating tissue destruction and angiogenesis and as 'frame-shots' of evidence in man supports. 3,[85][86][87] The cause of change from parainflammation to chronic inflammation remains unknown. We can however make inroads and unwrap possible mechanisms for AMD by comparing with immunemediated uveitis and the role of innate immunity and, in particular, macrophages.…”
Section: Understanding Uveitismentioning
confidence: 99%
“…The consequence is a switch to a more 'classical' chronic inflammatory responses propagating tissue destruction and angiogenesis and as 'frame-shots' of evidence in man supports. 3,[85][86][87] The cause of change from parainflammation to chronic inflammation remains unknown. We can however make inroads and unwrap possible mechanisms for AMD by comparing with immunemediated uveitis and the role of innate immunity and, in particular, macrophages.…”
Section: Understanding Uveitismentioning
confidence: 99%
“…Similar to T2DM and Alzheimer's disease, drusen consists of amyloid beta, a pro-inflammatory molecule that also activates complement [142] and the NLRP3 inflammasome [130,132]. Drusen components, complement C1q and oxidized lipids, activate the NLRP3 inflammasome resulting in increased production of the pro-inflammatory cytokines, IL-1 and IL-18 [156]. IL-18 is thought to protect against AMD by inhibiting VEGF and thus preventing the pathological neovascularization in wet AMD.…”
Section: Pdmentioning
confidence: 99%
“…94,95 Interestingly, a recent study has shown that isolated drusen harvested from AMD eyes have the ability to activate the inflammasome in bone marrow-derived macrophages with the release of both IL-18 and IL-1. 96 IL-18 has further been shown to promote RPE cell damage and atrophy (akin to dry AMD) 97 while there is also evidence that the IL-18 may be anti-angiogenic 96 and thus protective for wet AMD. It is intriguing to consider the possibility that the local secretion and tissue concentration of a single cytokine may determine the outcome and type of AMD and thus bear directly on visual prognosis (dry vs wet vs no AMD).…”
Section: Pathology Of Macular Degenerationmentioning
confidence: 99%